Development of an intervention for patients following an anterior cruciate ligament rupture: an online nominal group technique consensus study - Phillipa Logan; David Beard; Paul Leighton; Benjamin E Smith; Fiona Moffatt; Kate E Webster; Hayley Carter (BMJ Open)
Objectives (1) To develop an intervention for to support patients diagnosed with an anterior cruciate ligament (ACL) rupture with decision-making regarding treatment. (2) To define evidence-based recommendations for the treatment of patients following an ACL rupture.Design Nominal group technique consensus study.Setting Online meetings with patients and key stakeholders working and receiving treatment in the National Health Service, UK.Participants Consensus meetings composed of eight voting participants and five non-voting facilitators. Voting participants included five clinicians, one outpatient therapy manager and two patients with experience in an ACL rupture and reconstructive surgery. Non-voting facilitators supported group discussions and/or observed study procedures. This included a clinical academic expert, two methodology experts and two patient representatives.Method Two online meetings were held. Pre-elicitation material was distributed ahead of the first meeting. Premeeting voting was conducted ahead of both meetings. A draft of the shared decision-making intervention and recommendations were shared ahead of the second meeting. Components were discussed and ranked for inclusion based on a 70% agreement threshold.Results The meetings led to the development of a shared decision-making intervention to support treatment decision-making following an ACL rupture. The intervention includes two components: (1) a patient information leaflet and key questions diagram and (2) option grid. The evidence-based recommendations encompass core components of treatment reaching the 70% threshold agreed by the group. The recommendations cover: (1) advice and education, (2) exercise guidance, (3) intervention delivery, (4) outcome measure use and (5) shared decision-making.Conclusion This study has successfully developed a shared decision-making intervention to support ACL treatment decision-making, ready for testing in a future feasibility study. Evidence-based recommendations for the treatment of patients following ACL injury, ready for testing in a National Health Service (UK) setting, are also presented.Trial registration number NCT05529511.